THE IMPACT OF PROTON PUMP INHIBITORS ON KIDNEY FAILURE: LITERATURE REVIEW - Natalia Bednarczyk; Rafał Bednarczyk; Radosław Krzysztof Binkowski; Agnieszka Kurek; Natalia Krajewska; Aleksandra Lejman; Aleksandra Mazurkiewicz; Hubert Sidor; Monika Wołosik; Szymon Zysiak (International Journal of Innovative Technologies in Social Science, 2026)
Proton pump inhibitors (PPIs) are among the world’s most frequently prescribed medications for treating acid-related gastrointestinal disorders. Increasing evidence from the past decade has raised concerns about their potential adverse effects on kidney function. This review examines multiple dimensions of PPI-associated nephrotoxicity, including acute interstitial nephritis (AIN), acute kidney injury (AKI), chronic kidney disease (CKD), progression and end-stage renal disease (ESRD). Multiple observational studies and meta-analyses have demonstrated connections between PPI use and adverse renal outcomes. The underlying mechanisms remain incompletely understood. The evidence suggests that PPIs may contribute to kidney dysfunction through various pathways, including immune-mediated reactions, alterations in magnesium homeostasis, changes in renal blood flow, and potential effects on gut microbiome-derived uremic toxins. While some recent studies challenge the strength of these correlations, the weight of evidence indicates a need for more judicious PPI prescribing, particularly in patients with existing kidney disease or risk factors for renal dysfunction. This work provides healthcare professionals with an understanding of current evidence, proposed mechanisms, clinical implications, and recommendations for PPI use in the context of kidney health.